A comparative study of the use of selective digestive decontamination prophylaxis in living‐donor liver transplant recipients. Issue 4 (23rd May 2014) - Katchman, E.; Marquez, M.; Bazerbachi, F.; Grant, D.; Cattral, M.; Low, C.Y.; Renner, E.; Humar, A.; Selzner, M.; Ghanekar, A.; Rotstein, C.; Husain, S.
Abstract Introduction Bacterial infections are major causes of early morbidity and mortality after liver transplantation. Selective digestive decontamination (SDD) can be used pre‐operatively for living‐donor liver transplant (LD‐LT), but its role in this setting remains controversial. Methods To evaluate this strategy, we retrospectively analyzed a cohort of consecutive LD‐LTs performed in our center from March 2007 to February 2011 and compared the incidence and nature of early infectious complications, length of intensive care unit stay and hospitalization, antibiotic use, and emergence of resistant bacteria in patients with or without SDD prophylaxis. Results Of 148 LD‐LTs in the study period, 111 received SDD prophylaxis while 37 did not. In a multivariate model, the independent factors associated with an increased risk of early post‐transplant infections were length of postoperative mechanical ventilation (for every additional day odds ratio [OR] = 2.37, 95% confidence interval [CI] 1.4–4.0; P = 0.002), and choledochojejunostomy (OR = 4.5, 95% CI 1.95–10.5; P < 0.001). Use of SDD did not affect the rate or distribution of infectious complications, duration of hospitalization, antibiotic use, or acquisition of resistant bacteria (OR = 3.52, 95% CI 0.43–15.17; P = 0.376). Conclusion In conclusion, the use of SDD prophylaxis in LD‐LT was not beneficial and should be avoided, as it offers no advantage and could potentiate the emergence of multidrug‐resistant organisms.